Increasing Establishment of Non-native Fish Species in the Seine River Basin: Insights From Medium- and Long-Term Approaches - Belliard, Jérôme; Beslagic, Sarah; Boucault, Julien; Zahm, Amandine (Frontiers in Ecology and Evolution, 2021)
The spread of non-native species is nowadays recognized as a major threat to the biodiversity of freshwater ecosystems. However, for a very long time the introduction and acclimatization of new species has been perceived mainly as a source of wealth for human societies. Here, we examined the establishment of non-native fish species in the Seine River basin from a historical perspective by adopting a twofold approach. In a first step, at the whole basin scale, considering various written or archaeological sources, we traced the chronology, over the last millennium, of the establishments of non-native species. In a second step, by analyzing fish monitoring from several hundred sites covering the diversity of rivers and streams, we examined the changes in numbers and abundance of non-native species in local fish communities over the last three decades. The first documented species introduction dates back to the 13th century but it is from the middle of the 19th century that the introduction attempts accelerated. Today, these introductions have reached an unprecedented level and 46% of the species recorded in the basin are non-native. During the last three decades, non-native species have continued to increase within fish communities both in terms of number of species and abundance of individuals. The most pronounced increases are noted on large rivers and sites where anthropic pressures are strong. Waterways connecting European basins, globalization of trade, and coming climate change provide a general background suggesting that the increase in the proportion of non-native species in the fish communities of the Seine River basin is likely to continue for several decades.